2002
DOI: 10.1161/hs0302.104195
|View full text |Cite
|
Sign up to set email alerts
|

Functional Walk Tests in Individuals With Stroke

Abstract: Background and Purpose-Functional walk tests such as the 6-and 12-Minute Walk Test (ie, 6MWT and 12MWT, respectively) are submaximal measures used to determine functional capacity in individuals with compromised ability. The purpose of this study was to determine the relationship between these walk tests and measures of exertion (perceived and myocardial), in addition to impairment in individuals with stroke. The relationship among the 6MWT, 12MWT, and the more traditionally assessed measure of self-paced ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(90 citation statements)
references
References 39 publications
(33 reference statements)
4
78
1
5
Order By: Relevance
“…This association occurred at the expense of the patients' perception of their mobility. The simplicity of the 6MWT has led to its use in the assessment of patients with functional disability caused by neurologic disorders 17,18,29 . The mean walking distance obtained from our sample is on a par with the results put forward by Garber and Friedman 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association occurred at the expense of the patients' perception of their mobility. The simplicity of the 6MWT has led to its use in the assessment of patients with functional disability caused by neurologic disorders 17,18,29 . The mean walking distance obtained from our sample is on a par with the results put forward by Garber and Friedman 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The simplicity of the 6MWT has led to its use in the assessment of patients with functional disability caused by neurologic disorders 17,18 . However, few studies reported walking capacity during 6MWT in people with PD and these studies didn't assess how the patients perceive the reduction of mobility in QoL 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in persons with stroke where the correlation coefficient between gait speed and 6-minwalk distance was found to be as high as 0.92. 24 However, Eng et al 24 suggested that although the 6-minwalk distance may not provide different information from gait speed, monitoring the change in heart rate and blood pressure during the 6-min-walk test provided important information regarding an individual's myocardial exertion over the task. The change in hemodynamics may be a worthy measure to monitor during the 6-min-walk test in the future for individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, stroke patients may have trouble walking while shopping at a store, which is one of the instrumental activities of daily living (IADL). A study reported that gait function measurement is mainly carried out in a laboratory or other spaces in a hospital, and stroke patients are not provided with other environments in which they can try to adapt their gait to basic living conditions 12) . Laboratory and hospital environments are different from outdoor environments, and this leads to stroke patients having limited gait ability in their communities and low adaptability to home-dwelling because these environmental factors are not reflected in rehabilitation treatment 13) .…”
Section: Introductionmentioning
confidence: 99%